Bucculatrix crataega sp. nov. (Lepidoptera: Bucculatricidae), a leaf miner on Crataegus, representing the first formally named species of the family from mainland China - Liu, Tengteng; Wang, Hu (Zootaxa, 2019)
A new leaf-mining species of the genus Bucculatrix Zeller, 1839, B. crataega Liu, sp. nov., feeding on Crataegus pinnatifida Bunge is described herein, representing the first formally named species of Bucculatricidae from mainland China. Adult and genitalia of both sexes are described and illustrated. Host plant, leaf mine and cocoon are also illustrated. DNA barcode analysis supports the separation of B. crataega from related species.